LEGAL ASPECTS OF PROVING THE CRIME OF DEMOLITION BY AN UNKNOWN GROUP OF ADULTS - Nugraha, Rendy Pramudya (Jurnal Abdisci, 2025)
Abstract Background. Persecution is all unlawful acts and actions of a person to a person that harm or cause pain to the human body or limbs, which are injuries suffered by the victim. Aims. According to the doctrine, persecution has several elements, namely the existence of intentionality, deeds, and the consequences of the (intended) deed. Methods. These elements will distinguish what type of persecution is committed. The types of criminal acts are ordinary, light, planned, severe, heavily planned, persecution of certain quality people, or in a certain way incriminating. In practice, it is pretty difficult to distinguish between ordinary persecution and persecution. Result. The reason is that, in terms of evidence used, it only includes evidence in the form of Visum et Repertum from Victim Witnesses and statements from Witnesses. Conclusion. The conclusion is that the article is based on the defendant's act of committing a criminal act of persecution that resulted in the victim being injured. This act was carried out illegally. Implementation. Therefore, the defendant's article 351 paragraph (1) of the Criminal Code concerning persecution.